Safety car detection with notification system - Nur Fathihah, Mashudi (2019)
Safety Car Detection with Notification System is a mobile application combined with Arduino. This project built with Arduino Uno Microcontroller, temperature sensor, crash sensor, gas sensor, GPS module, GSM module, Bluetooth module and breadboard. This Safety Car Detection with Notification System will initiate, when this application installed in an android device and the Bluetooth is connected between the android and the Arduino sensors. Next, since there are three sensors used in this project, the notification will be send when they detect any of these three sensors, heat (when temperature of the car is exceeding 78℃), crash (when the car experienced crash) and gas(when the intensity volume of gas in the car exceed the limit stated). Then, a notification will be deliver to the number has been assigned, i.e. parent, ambulance and Malaysia Fire and Rescue Department. The notification will contain the information of what kind sensor detected and the coordination of accident location with the Google maps link. Safety Car Detection with Notification System developed since the number of people died at the location of accident due to the late information received at the family of accident victims, ambulance and Malaysia Fire and Rescue Department. Plus, most of the accident case occurred at rural area and route that has small number of people passed by. Plus, the Safety Car Detection with Notification System developed in order to ensure the rescue action will received in short of time, since this application will help to deliver information as soon as the accident occurred to the family of victims, ambulance and Malaysia Fire and Rescue Department.